APLIKASI PENGENALAN PAHLAWAN NASIONAL DI PULAU JAWA UNTUK SISWA SD BERBASIS ANDROID STUDI KASUS PADA SDN PONDOK PINANG 10 PAGI JAKARTA SELATAN - Indarti, Indarti (Jurnal Pilar Nusa Mandiri, 2017)
This research is motivated by the development of multimedia technology in various fields. The problems there is still a lot of education in Indonesia using the conventional method that is by listening to the teacher's explanations and using books, the method makes students easily bored. Therefore, was made a learning media by using interactive multimedia technology, so that students are more eager to learn. The purpose of making this learning media is to help students recognize heroes on the island of Java, which was developed with Adobe Flash Professional CS6 and Android Smartphones android. The author uses the method of data collection consists of literature studies, interviews, and distributing questionnaires. This research resulted in an interactive multimedia device that is able to combine text, pictures, audio and animation in one unit smartphones android, so it can support the learning process into a dynamic and interactive learning individual nature. Results of the test system, that a national hero introduction applications in Java have attracted the interest of students' to learn using interactive multimedia.